Race Traitor Treason to Whiteness is Loyalty to Humanity No. 8 - John Garvey:::Editor:::; Beth Henson:::Editor:::; Noel Ignatiev:::Editor:::; Sabra, Adam (editor):::::: (New Abolitionists Inc.)
Race Traitor aims to serve as an intellectual center for those seeking to abolish the white race. It will encourage dissent from the conformity that maintains it and popularize examples of defection from its ranks, analyze the forces that hold it together and those that promise to tear it apart. Part of its task will be to promote debate among abolitionists. When possible, it will support practical measures, guided by the principle, Treason to whiteness is loyalty to humanity.